Preparation method and application of ZIF-67 coated raised graphite nanosheet monatomic catalyst
Through the preparation of ZIF-67 coated convex graphite nanosheet single-atom catalyst, the shortcomings of existing catalysts in carrier mobility and mass transfer efficiency are solved, and efficient catalytic performance and good wastewater treatment effect are achieved.
Patent Information
- Application Number
- CN202411750767.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing catalysts have shortcomings in charge transport performance, carrier concentration and migration efficiency, especially when treating persistent macromolecular organic pollutants in wastewater, the mass transfer efficiency is low, affecting the catalytic performance.
Using the preparation method of ZIF-67 coated with convex graphite nanosheets, a new single-atom cobalt catalyst anchored on three-dimensional porous carbon materials was developed by mesoporously expanded graphite and ZIF-67 as precursors.
It significantly improves carrier mobility and mass transfer efficiency, enhances the accessibility of metal sites, improves catalytic performance, has significant catalytic oxidation effect on a variety of dyes, and shows good removal effect in real wastewater.
Smart Images

Figure CN119565610A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a catalyst. Background Art
[0002] Isolated metal atoms are prone to migration and aggregation due to their increased surface energy, thus forming metal clusters. Metal clusters change the electronic structure and distribution of active sites due to their aggregation, thereby reducing the catalytic performance of the catalyst. Current studies have found that supporting metal single atoms on a specific substrate is an effective way to reduce atomic aggregation and stabilize single metal atoms. However, how to bind metal single atoms to a fixed substrate and make the medium transmission unobstructed is a difficult problem that needs to be solved urgently. At present, molecular channels in porous materials such as molecular sieves and metal organic frameworks (MOFs) are used as "cages" to restrict the migration of metal atoms. The confinement inside nanoporous materials can precisely control the metal coordination environment, electronic properties, and the size and distribution of metal atoms, which helps to improve selectivity and catalytic performance. However, the relatively small pore size limits the diffusion and encapsulation of larger organic molecules in the internal pore network, especially persistent macromolecular organic pollutants in wastewater, which seriously affects the mass transfer efficiency in the catalytic process. Therefore, in order to optimize the catalytic performance, it is necessary to explore an effective material synthesis method that can not only improve the carrier mobility and mass transfer efficiency, but also improve the accessibility of metal sites in the catalytic process. The advanced oxidation treatment process of persistent organic pollutants in wastewater also urgently needs an efficient catalyst with good catalytic effect in real wastewater. Summary of the invention
[0003] The purpose of the present invention is to solve the negative impact of the charge transport performance of existing catalysts, the low carrier concentration and the poor carrier migration efficiency, and to provide a preparation method and application of a ZIF-67 coated protruding graphite nanosheet single atom catalyst.
[0004] A method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst is specifically completed by the following steps:
[0005] 1. Preparation of expanded graphite:
[0006] ①, ammonium persulfate and concentrated sulfuric acid are mixed evenly, then natural flake graphite is added, and then stirred at room temperature for a period of time to obtain natural flake graphite slurry; the natural flake graphite slurry is allowed to stand at room temperature for a period of time, then washed with distilled water, and vacuum dried to obtain expandable graphite with a worm-like structure;
[0007] ②, transfer the expandable graphite with worm-like structure to a porcelain boat, and then place it in the temperature zone of a tubular furnace, introduce nitrogen, heat the expandable graphite with worm-like structure to 600°C, and keep it at 600°C for a period of time to obtain expanded graphite;
[0008] 2. Preparation of ZIF-67-x@EG composite materials:
[0009] ①, add expanded graphite and polyvinyl pyrrolidone into methanol and stir for a period of time to obtain solution A;
[0010] ②. Put Co(NO 3 ) 2 6H 2 O is added to methanol and stirred for a period of time to obtain solution B;
[0011] ③. Add 2-methylimidazole to methanol and stir for a period of time to obtain solution C;
[0012] ④. Add solution B and solution C to solution A, stir magnetically for a period of time at room temperature to obtain a mixture; transfer the mixture to an autoclave lined with polytetrafluoroethylene, heat it to 110°C, perform hydrothermal reaction at 110°C for a period of time, and then cool it to room temperature to obtain a reaction product;
[0013] ⑤. Using anhydrous ethanol as a cleaning agent, the reaction product is centrifuged and cleaned, and then the solid matter after centrifugation is collected and dried to obtain a cleaned solid product;
[0014] ⑥. The cleaned solid product was transferred to a tubular furnace, and then heated to 600°C under the protection of a nitrogen atmosphere, and carbonized at 600°C for a period of time to obtain a ZIF-67-coated protruding graphite nanosheet single atom catalyst.
[0015] A ZIF-67-coated protruding graphene nanosheet single-atom catalyst was used to catalyze the degradation of micropollutants in water by persulfate.
[0016] Beneficial effects of the present invention:
[0017] (1) The present invention uses mesoporous expanded graphite (EG) and ZIF-67 as precursors to develop a new single-atom cobalt catalyst anchored on a three-dimensional porous carbon material (ZIF-67-x@EG);
[0018] (2) The ZIF-67-coated protruding graphite nanosheet single-atom catalyst prepared by the present invention introduces cobalt atoms into the protrusions formed by EG to increase the carrier concentration and significantly improve the carrier mobility;
[0019] (3) The ZIF-67-coated protruding graphite nanosheet single-atom catalyst (ZIF-67-x@EG catalyst) prepared by the present invention has a mesoporous structure, which improves the carrier mobility and mass transfer efficiency, and improves the accessibility of metal sites during the catalytic process, and has a significant catalytic oxidation effect on a variety of dyes;
[0020] (4) Cobalt atoms can expand pores, generate mesopores, and optimize electron transfer pathways; the deformation of the protrusions increases the carrier concentration exponentially, and due to the introduction of cobalt atoms, the carrier mobility is significantly improved;
[0021] (5) The ZIF-67-x@EG catalyst prepared by the present invention is used in combination with persulfate, and the removal efficiency of levofloxacin (24 mg / L, 48 mg / L) is as high as 95% within 10 minutes, and the removal efficiency of levofloxacin (72 mg / L) is as high as 77% or more within 10 minutes;
[0022] (6) The ZIF-67-x@EG catalyst prepared by the present invention has a good removal effect on levofloxacin antibiotics, active yellow dyes, carbamazepine, bisphenol A, rhodamine B, etc.
[0023] The invention can obtain a ZIF-67 coated protruding graphite nanosheet single atom catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron micrograph of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0025] Figure 2 TEM image of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0026] Figure 3 HETEM image of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0027] Figure 4 This is the HAADF diagram of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0028] Figure 5 for Figure 1 EDX element mapping of the selected area in the image;
[0029] Figure 6 This is the XANES graph of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0030] Figure 7 FT k3-weighted EXAFS graph of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0031] Figure 8 This is the XPS spectrum of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0032] Fig. 9 The N of ZIF-67-1@EG prepared in step 2 (6) of Example 12 Adsorption-desorption isotherm plot;
[0033] Fig.10 The effect diagram of levofloxacin degradation in application tests 1 to 7;
[0034] Fig.11 The degradation kinetics of levofloxacin were investigated using experiments 1 to 7;
[0035] Fig.12 The degradation kinetics of high concentration levofloxacin were investigated using experiments 1 to 7;
[0036] Fig.13 is the degradation kinetics under the conditions of inorganic anions and humic acid;
[0037] Fig.14 Degradation kinetics of different pollutants for application test 8;
[0038] Fig.15 This is a diagram showing the effect of reusing the ZIF-67 coated protruding graphene nanosheet single atom catalyst prepared in Example 1 to degrade levofloxacin. In the figure, Used means the used catalyst, Re-calcined means the re-calcined catalyst, and st For first time use, 2 nd For the second use, 3 rd For the third use, 4 th For the fourth use, 5 th For the fifth use. DETAILED DESCRIPTION
[0039] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
[0040] Specific implementation method 1: This implementation method is a method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst, which is specifically completed by the following steps:
[0041] 1. Preparation of expanded graphite:
[0042] ①, ammonium persulfate and concentrated sulfuric acid are mixed evenly, then natural flake graphite is added, and then stirred at room temperature for a period of time to obtain natural flake graphite slurry; the natural flake graphite slurry is allowed to stand at room temperature for a period of time, then washed with distilled water, and vacuum dried to obtain expandable graphite with a worm-like structure;
[0043] ②, transfer the expandable graphite with worm-like structure to a porcelain boat, and then place it in the temperature zone of a tubular furnace, introduce nitrogen, heat the expandable graphite with worm-like structure to 600°C, and keep it at 600°C for a period of time to obtain expanded graphite;
[0044] 2. Preparation of ZIF-67-x@EG composite materials:
[0045] ①, add expanded graphite and polyvinyl pyrrolidone into methanol and stir for a period of time to obtain solution A;
[0046] ②. Put Co(NO 3 ) 2 6H 2 O is added to methanol and stirred for a period of time to obtain solution B;
[0047] ③. Add 2-methylimidazole to methanol and stir for a period of time to obtain solution C;
[0048] ④. Add solution B and solution C to solution A, stir magnetically for a period of time at room temperature to obtain a mixture; transfer the mixture to an autoclave lined with polytetrafluoroethylene, heat it to 110°C, perform hydrothermal reaction at 110°C for a period of time, and then cool it to room temperature to obtain a reaction product;
[0049] ⑤. Using anhydrous ethanol as a cleaning agent, the reaction product is centrifuged and cleaned, and then the solid matter after centrifugation is collected and dried to obtain a cleaned solid product;
[0050] ⑥. The cleaned solid product was transferred to a tubular furnace, and then heated to 600°C under the protection of a nitrogen atmosphere, and carbonized at 600°C for a period of time to obtain a ZIF-67-coated protruding graphite nanosheet single atom catalyst.
[0051] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that: the natural flake graphite described in step 1① is 2H phase nano flake graphite sheet, the particle diameter is 100nm~800nm, and has 50 layers~60 layers of carbon atoms; the mass volume ratio of ammonium persulfate, natural flake graphite and concentrated sulfuric acid described in step 1① is (1g~5g):(4g~20g):(1mL~4mL). The other steps are the same as specific embodiment 1.
[0052] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the stirring time at room temperature in step 1① is 5min to 10min; distilled water is used to wash to neutrality in step 1①; the natural flake graphite slurry in step 1① is left to stand at room temperature for 20h to 24h; the vacuum drying temperature in step 1① is 70℃ to 80℃, and the vacuum drying time is 10h to 12h. The other steps are the same as those in specific implementation method one or two.
[0053] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the heating rate described in step 1 ② is 5 ℃ / min ~ 10 ℃ / min; the insulation time at 600 ℃ in step 1 ② is 2h ~ 4h; the mass ratio of expanded graphite and polyvinyl pyrrolidone described in step 2 ① is (1g ~ 5g): (0.1g ~ 0.5g); the volume ratio of the total mass of expanded graphite and polyvinyl pyrrolidone described in step 2 ① to methanol is (0.5g ~ 1.5g): 25mL; the Co(NO 3 ) 2 6H 2 The mass ratio of O to the volume ratio of methanol is (0.5 g to 1.23 g): 25 mL; the mass ratio of 2-methylimidazole described in step 2 (3) to the volume ratio of methanol is (0.5 g to 1.23 g): 25 mL; the stirring time described in step 2 (1), (2) and (3) is 5 min to 10 min. The other steps are the same as those in specific embodiments 1 to 3.
[0054] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that: the volume ratio of solution B, solution C and solution A described in step 2 ④ is 1:1:1; the heating rate described in step 2 ④ is 5℃ / min~10℃ / min; the cooling rate described in step 2 ④ is 1℃ / min~8℃ / min; the speed of magnetic stirring at room temperature in step 2 ④ is 150r / min~200r / min, and the time of magnetic stirring is 20min~40min; the time of hydrothermal reaction at 110℃ in step 2 ④ is 10h~12h. The other steps are the same as those in specific implementation modes 1 to 4.
[0055] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that: in step 2 ⑤, the reaction product is centrifugally cleaned with anhydrous ethanol as a cleaning agent until the liquid has no obvious purple color; the speed of the centrifugal cleaning described in step 2 ⑤ is 5000r / min, and the time of each centrifugal cleaning is 5min~10min; the drying temperature described in step 2 ⑤ is 70℃~90℃, and the drying time is 10h~14h; the carbonization time at 600℃ in step 2 ⑥ is 2h~3h; the heating rate described in step 2 ⑥ is 5℃ / min~10℃ / min. The other steps are the same as specific implementation methods 1 to 5.
[0056] Specific embodiment seven: This embodiment is a ZIF-67 coated protruding graphite nanosheet single atom catalyst used to catalyze the degradation of micropollutants in water with persulfate.
[0057] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the micropollutant is one or a mixture of levofloxacin series antibiotics, carbamazepine, bisphenol A, rhodamine B and reactive yellow series dyes. The other steps are the same as those of specific embodiments one to seven.
[0058] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the persulfate is peroxymonosulfate, peroxydisulfate or sulfite. The other steps are the same as those of specific embodiments 1 to 8.
[0059] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: a ZIF-67 coated protruding graphite nanosheet single atom catalyst is used to catalyze the degradation of micropollutants in water by persulfate, which is specifically completed in the following steps:
[0060] The ZIF-67 coated protruding graphite nanosheet single atom catalyst and persulfate are added to wastewater containing micropollutants and degraded for a period of time to obtain water free of micropollutants.
[0061] The dosage of the ZIF-67 coated protruding graphite nanosheet single atom catalyst is 0.1 g / L to 0.8 g / L, and the dosage of the persulfate is 0.1 g / L to 0.8 g / L;
[0062] The concentration of micropollutants in the wastewater containing micropollutants is 12 mg / L to 72 mg / L;
[0063] The degradation time is 10 to 60 minutes. The other steps are the same as those in the first to ninth embodiments.
[0064] The following examples are used to verify the beneficial effects of the present invention:
[0065] Example 1: A method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst, which is specifically completed by the following steps:
[0066] 1. Preparation of expanded graphite:
[0067] ①, 5g of ammonium persulfate and 3mL of concentrated sulfuric acid (mass fraction of 98%) were mixed evenly, and then 5g of natural flake graphite was added, and then stirred at room temperature for 5min to obtain natural flake graphite slurry; the natural flake graphite slurry was allowed to stand at room temperature for 24h, and then centrifuged and washed with distilled water until neutral, and then vacuum dried at 77°C for 12h to obtain expandable graphite with a worm-like structure;
[0068] The natural flake graphite described in step 1① is a 2H phase nano flake graphite sheet with a particle diameter of 100nm to 800nm and 50 to 60 layers of carbon atoms;
[0069] ②, transfer the expandable graphite with a worm-like structure to a porcelain boat, and then place it in the temperature zone of a tubular furnace, introduce nitrogen, heat the expandable graphite with a worm-like structure to 600°C, and keep it at 600°C for 2 hours to obtain expanded graphite;
[0070] The heating rate described in step 1② is 5°C / min;
[0071] 2. Preparation of ZIF-67-x@EG composite materials:
[0072] ①, add 1.0g expanded graphite and 0.5g polyvinyl pyrrolidone into 25mL methanol, stir for 10min, and obtain solution A;
[0073] ②, 1.23gCo(NO 3 ) 2 6H 2 O was added into 25 mL of methanol and stirred for 10 min to obtain solution B;
[0074] ③. Add 1.23 g of 2-methylimidazole to 25 mL of methanol and stir for 10 min to obtain solution C;
[0075] ④. Add solution B and solution C to solution A, stir magnetically for 30 min at room temperature at a speed of 200 r / min to obtain a mixture; transfer the mixture to an autoclave lined with polytetrafluoroethylene, heat it to 110° C., perform hydrothermal reaction at 110° C. for 12 h, and then cool it to room temperature to obtain a reaction product;
[0076] The volume ratio of solution B, solution C and solution A described in step 2④ is 1:1:1;
[0077] The heating rate in step 2④ is 5°C / min;
[0078] The cooling rate described in step 2④ is 3°C / min;
[0079] ⑤. Use anhydrous ethanol as a cleaning agent to centrifuge and clean the reaction product until the liquid has no obvious purple color, then collect the solid matter after centrifugation, dry the solid matter, and obtain a cleaned solid product;
[0080] The speed of the centrifugal washing described in step 2⑤ is 5000r / min, and the time of each centrifugal washing is 5min;
[0081] The drying temperature in step 2⑤ is 80°C and the drying time is 10h;
[0082] ⑥ The cleaned solid product was transferred to a tube furnace, and then heated to 600°C under nitrogen atmosphere, and carbonized at 600°C for 2h to obtain a ZIF-67-coated protruding graphite nanosheet single atom catalyst, which was recorded as ZIF-67-0.5@EG catalyst;
[0083] The heating rate described in step 2⑥ is 5°C / min.
[0084] Example 2: The difference between this example and Example 1 is that in step 2②, 2.46 g Co(NO 3 ) 2 6H 2 O was added to 25 mL of methanol and stirred for 10 min to obtain solution B; in step 2③, 2.46 g of 2-methylimidazole was added to 25 mL of methanol and stirred for 10 min to obtain solution C; the ZIF-67-coated protruding graphite nanosheet single atom catalyst obtained in step 2⑥ was recorded as ZIF-67-1@EG catalyst. The other steps and parameters were the same as those in Example 1.
[0085] Example 3: The difference between this example and Example 1 is that in step 2②, 3.69gCo(NO 3 ) 2 6H 2 O was added to 25 mL of methanol and stirred for 10 min to obtain solution B; in step 2③, 3.69 g of 2-methylimidazole was added to 25 mL of methanol and stirred for 10 min to obtain solution C; the ZIF-67-coated protruding graphite nanosheet single atom catalyst obtained in step 2⑥ was recorded as ZIF-67-1.5@EG catalyst. The other steps and parameters were the same as those in Example 1.
[0086] Example 4: The difference between this example and Example 1 is that in step 2②, 4.92gCo(NO 3 ) 2 6H 2O was added to 25 mL of methanol and stirred for 10 min to obtain solution B; in step 2③, 4.92 g of 2-methylimidazole was added to 25 mL of methanol and stirred for 10 min to obtain solution C; the ZIF-67-coated protruding graphite nanosheet single atom catalyst obtained in step 2⑥ was recorded as ZIF-67-2@EG catalyst. The other steps and parameters were the same as those in Example 1.
[0087] Figure 1 This is a scanning electron micrograph of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0088] from Figure 1 It can be seen that after loading ZIF-67, the smooth wrinkled surface of expanded graphite (EG) with multi-layer curled flakes becomes rough and presents a fluffy porous structure, which effectively increases the contact area between ZIF-67 nanoparticles and the substrate surface, and ultimately enhances their dispersibility. This compact structure can shorten the carrier transport distance, provide excellent electron transport performance, and expose the catalytic surface area, thereby increasing the accessibility of active sites and ultimately improving the catalytic performance.
[0089] Figure 2 TEM image of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0090] Figure 3 HETEM image of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0091] from Figure 3 It can be seen that at the interlayer spacing of 0.295 nm, the carbon graphite (102) plane is observed to match the lattice fringes. Correspondingly, the interlayer spacings of 0.252 nm and 0.295 nm correspond to the (2 03) and (20 4) planes of Co.
[0092] Figure 4 This is the HAADF diagram of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0093] from Figure 4 This reflects the fact that a single Co atom is smaller than The metals are uniformly dispersed within a radius of , and no metal clusters are detected on the surface of ZIF-67-1@EG.
[0094] Figure 5 for Figure 1 EDX element mapping of the selected area in the image;
[0095] Figure 5 The uniform distribution of C, N, O and Co was confirmed.
[0096] Figure 6This is the XANES graph of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0097] from Figure 6 It can be seen that the absorption edge of ZIF-67-1@EG is located between Co foil and CoO, indicating that the valence state of Co atoms is between 0 and +2, and a single Co atom coordinates with four pyridine nitrogen atoms to form a Co-N 4 Bit.
[0098] Figure 7 FT k3-weighted EXAFS graph of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0099] from Figure 7 It is known that in There is a main peak at , which is caused by Co-N coordination scattering.
[0100] Figure 8 This is the XPS spectrum of ZIF-67-1@EG prepared in step 2⑥ of Example 1;
[0101] from Figure 8 It can be seen that Co, O, C, and N elements exist in the ZIF-67-x@EG composite material.
[0102] Fig. 9 The N of ZIF-67-1@EG prepared in step 2 (6) of Example 1 2 Adsorption-desorption isotherm plot;
[0103] from Fig. 9 It can be seen that N 2 The adsorption-desorption isotherm showed that the specific surface area of ZIF-67-x@EG was 16.26 m 2 / g, BJH pore volume is 0.089dm 3 / g, and the average pore size is 21.94nm.
[0104] Application test 1: Under natural light conditions, natural flake graphite (NG) and potassium permonosulfate (PMS) were added to wastewater containing levofloxacin LEVO at a pH value of 3.8, and then degraded for 0 min to 45 min under stirring conditions to obtain wastewater from which levofloxacin LEVO was removed;
[0105] The addition amount of the natural flake graphite is 0.4 g / L, and the addition amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0106] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L.
[0107] Application test 2: Under natural light conditions, nitrogen-doped flake graphite (NG@N) (1 g of graphite nanosheets and 5 g of urea were fully ground, placed in a magnetic boat, placed in a tube furnace, pyrolyzed at 600°C for 4 hours under a nitrogen atmosphere, and taken out for standby use after the system was cooled) and potassium permonosulfate (PMS) were added to wastewater containing levofloxacin LEVO at a pH of 3.8, and then degraded for 0 min to 45 min under stirring to obtain wastewater from which levofloxacin LEVO was removed;
[0108] The addition amount of the nitrogen-doped flake graphite (NG@N) is 0.4 g / L, and the addition amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0109] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L.
[0110] Application test 3: Under natural light conditions, expanded graphite (EG) catalyst and potassium permonosulfate (PMS) were added to wastewater containing levofloxacin LEVO at a pH value of 3.8, and then degraded for 0 min to 45 min under stirring conditions to obtain wastewater from which levofloxacin LEVO was removed;
[0111] The added amount of the expanded graphite catalyst is 0.4 g / L, and the added amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0112] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L.
[0113] Application test 4: Under natural light conditions, nitrogen-doped expanded graphite (EG@N) catalyst (1 g of the expanded graphite nanosheets EG prepared in Example 1 and 5 g of urea were fully ground, placed in a magnetic boat, placed in a tube furnace, and pyrolyzed at 600° C. for 4 hours under a nitrogen atmosphere. After the system was cooled, it was taken out for use) and potassium permonosulfate (PMS) were added to wastewater containing levofloxacin LEVO with a pH value of 3.8, and then degraded for 0 min to 45 min under stirring to obtain wastewater from which levofloxacin LEVO was removed;
[0114] The added amount of the expanded graphite catalyst is 0.4 g / L, and the added amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0115] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L.
[0116] Application test 5: Under natural light conditions, ZIF-67 doped flake graphite (ZIF-67 / NG) catalyst and potassium permonosulfate (PMS) were added to wastewater containing levofloxacin LEVO at a pH of 3.8, and then degraded for 0 min to 45 min under stirring conditions to obtain wastewater from which levofloxacin LEVO was removed;
[0117] The addition amount of the ZIF-67 doped flake graphite (ZIF-67 / NG) catalyst is 0.4 g / L, and the addition amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0118] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L;
[0119] The preparation method of the ZIF-67 doped flake graphite (ZIF-67 / NG) catalyst is specifically completed according to the following steps:
[0120] ①, add 1.0g natural flake graphite (NG) and 0.5g polyvinyl pyrrolidone into 25mL methanol and stir for 10min to obtain solution A;
[0121] ②, 1.23gCo(NO 3 ) 2 6H 2 O was added into 25 mL of methanol and stirred for 10 min to obtain solution B;
[0122] ③. Add 1.23 g of 2-methylimidazole to 25 mL of methanol and stir for 10 min to obtain solution C;
[0123] ④. Add solution B and solution C to solution A, stir magnetically for 30 min at room temperature at a speed of 200 r / min to obtain a mixture; transfer the mixture to an autoclave lined with polytetrafluoroethylene, heat it to 110° C., perform hydrothermal reaction at 110° C. for 12 h, and then cool it to room temperature to obtain a reaction product;
[0124] The volume ratio of solution B, solution C and solution A described in step ④ is 1:1:1;
[0125] The heating rate in step ④ is 5°C / min;
[0126] The cooling rate in step ④ is 3°C / min;
[0127] ⑤. Use anhydrous ethanol as a cleaning agent to centrifuge and clean the reaction product until the liquid has no obvious purple color, then collect the solid matter after centrifugation, dry the solid matter, and obtain a cleaned solid product;
[0128] The speed of the centrifugal washing in step ⑤ is 5000r / min, and the time of each centrifugal washing is 5min;
[0129] The drying temperature in step ⑤ is 80° C. and the drying time is 10 h;
[0130] ⑥ The cleaned solid product was transferred to a tube furnace, and then heated to 600°C under a nitrogen atmosphere, and carbonized at 600°C for 2h to obtain a ZIF-67 doped flake graphite (ZIF-67 / NG) catalyst;
[0131] The heating rate described in step ⑥ is 5°C / min.
[0132] Application test 6: Under natural light conditions, the ZIF-67-coated protruding graphite nanosheet single atom catalyst (ZIF-67-x@EG) and potassium permonosulfate (PMS) prepared in Examples 1 to 4 were respectively added to wastewater containing levofloxacin LEVO at a pH value of 3.8, and then degraded for 0 min to 45 min under stirring conditions to obtain wastewater from which levofloxacin LEVO was removed;
[0133] The addition amount of the ZIF-67 coated protruding graphite nanosheet single atom catalyst (ZIF-67-x@EG) is 0.4 g / L, and the addition amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0134] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L.
[0135] Application test 7: under natural light conditions, potassium permonosulfate (PMS) was added to wastewater containing levofloxacin LEVO at a pH value of 3.8, and then degraded for 0 min to 45 min under stirring conditions to obtain wastewater from which levofloxacin LEVO was removed;
[0136] The amount of potassium permonosulfate (PMS) added is 0.4 g / L;
[0137] The concentration of levofloxacin LEVO in the wastewater containing levofloxacin LEVO is 24 mg / L.
[0138] Fig.10 The effect diagram of levofloxacin degradation in application tests 1 to 7;
[0139] from Fig.10It can be seen that in the absence of potassium monopersulfate (PMS), the static adsorption efficiencies of EG, EG@N, and ZIF-67-x@EG for LEVO are 8.05%, 20.67%, and 11.13 - 18.34% respectively; when only PMS is introduced into the reaction system, even after 30 min, only 6.56% of LEVO is removed from the PMS system.
[0140] Fig.11 For the degradation kinetics of levofloxacin in Application Tests 1 - 7;
[0141] From Fig.11 it can be seen that the order of the pseudo-first-order rate constants (k obs ) of different catalysts is ZIF-67-0.5@EG < ZIF-67-1.5@EG < ZIF-67-2@EG < ZIF-67-1@EG. Among them, the k obs value of ZIF-67-1@EG is the highest, being 0.196 min -1 , which are 2.55 times and 2.33 times that of ZIF-67-0.5@EG (0.077 min -1 ) and ZIF-67-1.5@EG (0.084 min -1 ) respectively.
[0142] Fig.12 For the degradation kinetics of high-concentration levofloxacin in Application Tests 1 - 7;
[0143] From Fig.12 it can be seen that the removal efficiencies of the ZIF-67-1@EG catalyst for 48 mg / L and 72 mg / L of LEVO within 10 min are 90.63% and 51.98% respectively.
[0144] Fig.13 For the degradation kinetics under the conditions of inorganic anions and humic acid;
[0145] From Fig.13 it can be seen that Cl - and NO 3 - have a significant inhibitory effect on the catalytic system, while the effects of H 2 PO 4 - and humic acid (HA) are relatively small.
[0146] Application Test 8: Degrading different pollutants using the ZIF-67-coated convex graphite nanosheet single-atom catalyst prepared in Example 1 was specifically completed according to the following steps:
[0147] The ZIF-67 coated protruding graphite nanosheet single atom catalyst and potassium permonosulfate (PMS) prepared in Example 1 were added to wastewater containing micropollutants at a pH value of 3.8, and then degraded for 0 min to 120 min under stirring to obtain wastewater with micropollutants removed;
[0148] The addition amount of the ZIF-67 coated protruding graphite nanosheet single atom catalyst is 0.4 g / L, and the addition amount of potassium permonosulfate (PMS) is 0.4 g / L;
[0149] The concentrations of rhodamine B (RhB), carbamazepine (CBZ), reactive yellow (YR), bisphenol A (BPA) and levofloxacin (LEVO) in the wastewater containing micropollutants are all 24 mg / L.
[0150] Fig.14 Degradation kinetics of different pollutants for application test 8;
[0151] from Fig.14 It can be seen that the ZIF-67-1@EG / PMS system completely removed rhodamine B (RhB), carbamazepine (CBZ), reactive yellow (YR), bisphenol A (BPA) and levofloxacin (LEVO) within 10 minutes, and the removal efficiency of BPA within 30 minutes was 62.14%. The removal rate of RhB within 1 minute was about 100%, and the removal rate of k obs 1.93min -1 .
[0152] The ZIF-67 coated protruding graphite nanosheet single atom catalyst prepared in Example 1 was repeatedly used to degrade levofloxacin. Fig.15 As shown;
[0153] Fig.15 This is a diagram showing the effect of reusing the ZIF-67 coated protruding graphene nanosheet single atom catalyst prepared in Example 1 to degrade levofloxacin. In the figure, Used means the used catalyst, Re-calcined means the re-calcined catalyst, and st For first time use, 2 nd For the second use, 3 rd For the third use, 4 th For the fourth use, 5 th For the fifth use;
[0154] from Fig.15 It can be seen that when using ZIF-67-1@EG catalyst, the removal rate of LEVO gradually decreased in five cycles. In the first cycle, the removal rate was 99.40%, and in the fifth cycle, the removal rate dropped to 42.86%, k obs From 0.030min-1 Down to 0.010min -1 After the 1st, 3rd, and 5th cycles, the samples were washed with deionized water for 3 times and then heated at 600 °C in N 2 Heating for 2 h under atmosphere removed the intermediate products accumulated on the catalyst surface and restored its performance. Then, the catalytic performance was significantly restored, and the LEVO removal rates of the 1st, 3rd, and 5th cycles reached 80.05%, 75.49%, and 57.06%, respectively.
Claims
1. A method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of expanded graphite: ①, ammonium persulfate and concentrated sulfuric acid are mixed evenly, then natural flake graphite is added, and then stirred at room temperature for a period of time to obtain natural flake graphite slurry; the natural flake graphite slurry is allowed to stand at room temperature for a period of time, then washed with distilled water, and vacuum dried to obtain expandable graphite with a worm-like structure; ②, transfer the expandable graphite with worm-like structure to a porcelain boat, and then place it in the temperature zone of a tubular furnace, introduce nitrogen, heat the expandable graphite with worm-like structure to 600°C, and keep it at 600°C for a period of time to obtain expanded graphite; 2. Preparation of ZIF-67-x@EG composite materials: ①, add expanded graphite and polyvinyl pyrrolidone into methanol and stir for a period of time to obtain solution A; ②. Add Co(NO3)2·6H2O to methanol and stir for a while to obtain solution B; ③. Add 2-methylimidazole to methanol and stir for a period of time to obtain solution C; ④. Add solution B and solution C to solution A, stir magnetically for a period of time at room temperature to obtain a mixture; transfer the mixture to an autoclave lined with polytetrafluoroethylene, heat it to 110°C, perform hydrothermal reaction at 110°C for a period of time, and then cool it to room temperature to obtain a reaction product; ⑤. Using anhydrous ethanol as a cleaning agent, the reaction product is centrifuged and cleaned, and then the solid matter after centrifugation is collected and dried to obtain a cleaned solid product; ⑥. The cleaned solid product was transferred to a tubular furnace, and then heated to 600°C under the protection of a nitrogen atmosphere, and carbonized at 600°C for a period of time to obtain a ZIF-67-coated protruding graphite nanosheet single atom catalyst.
2. The method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 1, characterized in that The natural flake graphite described in step 1① is 2H phase nano flake graphite with a particle diameter of 100nm to 800nm and 50 to 60 layers of carbon atoms; the mass volume ratio of ammonium persulfate, natural flake graphite and concentrated sulfuric acid described in step 1① is (1g to 5g): (4g to 20g): (1mL to 4mL).
3. The method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 1, characterized in that The stirring time at room temperature in step 1① is 5min to 10min; distilled water is used to wash to neutrality in step 1①; the natural flake graphite slurry in step 1① is allowed to stand at room temperature for 20h to 24h; the vacuum drying temperature in step 1① is 70℃ to 80℃, and the vacuum drying time is 10h to 12h.
4. The method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 1, characterized in that The heating rate described in step 1 ② is 5°C / min~10°C / min; the insulation time of step 1 ② at 600°C is 2h~4h; the mass ratio of expanded graphite and polyvinyl pyrrolidone described in step 2 ① is (1g~5g):(0.1~0.5g); the volume ratio of the total mass of expanded graphite and polyvinyl pyrrolidone described in step 2 ① to methanol is (0.5g~1.5g):25mL; the mass ratio of Co(NO3)2·6H2O described in step 2 ② to methanol is (0.5g~1.23g):25mL; the mass ratio of 2-methylimidazole described in step 2 ③ to methanol is (0.5g~1.23g):25mL; the stirring time described in step 2 ①, ② and ③ is 5min~10min.
5. The method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 1, characterized in that The volume ratio of solution B, solution C and solution A described in step 2④ is 1:1:1; the heating rate described in step 2④ is 5℃ / min~10℃ / min; the cooling rate described in step 2④ is 1℃ / min~8℃ / min; the magnetic stirring speed at room temperature in step 2④ is 150r / min~200r / min, and the magnetic stirring time is 20min~40min; the hydrothermal reaction time at 110℃ in step 2④ is 10h~12h.
6. The method for preparing a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 1, characterized in that In step 2⑤, the reaction product is centrifugally cleaned with anhydrous ethanol as a cleaning agent until the liquid has no obvious purple color; the centrifugal cleaning speed described in step 2⑤ is 5000r / min, and the time of each centrifugal cleaning is 5min~10min; the drying temperature described in step 2⑤ is 70℃~90℃, and the drying time is 10h~14h; the carbonization time at 600℃ in step 2⑥ is 2h~3h; the heating rate described in step 2⑥ is 5℃ / min~10℃ / min.
7. Use of a ZIF-67 coated protruding graphite nanosheet single atom catalyst prepared by the preparation method according to claim 1, characterized in that A ZIF-67-coated protruding graphene nanosheet single-atom catalyst was used to catalyze the degradation of micropollutants in water by persulfate.
8. The use of a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 7, characterized in that The micro-pollutant is one or a mixture of several of levofloxacin series antibiotics, carbamazepine, bisphenol A, rhodamine B and reactive yellow series dyes.
9. The use of a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 7, characterized in that The persulfate is peroxymonosulfate, peroxydisulfate or sulfite.
10. The use of a ZIF-67 coated protruding graphite nanosheet single atom catalyst according to claim 7, characterized in that A ZIF-67 coated protruding graphite nanosheet single atom catalyst is used to catalyze the degradation of micropollutants in water by persulfate, which is specifically completed in the following steps: The ZIF-67 coated protruding graphite nanosheet single atom catalyst and persulfate are added to wastewater containing micropollutants and degraded for a period of time to obtain water free of micropollutants. The dosage of the ZIF-67 coated protruding graphite nanosheet single atom catalyst is 0.1 g / L to 0.8 g / L, and the dosage of the persulfate is 0.1 g / L to 0.8 g / L; The concentration of micropollutants in the wastewater containing micropollutants is 12 mg / L to 72 mg / L; The degradation time is 10 minutes to 60 minutes.
Citation Information
Patent Citations
Preparation method and application of iron disulfide-molybdenum carbide aerogel catalyst
CN114177926A
Graphene oxide coated ZIF-67 derived iron / cobalt / nitrogen / co-doped porous carbon nanoparticle composite material
CN114204048A
Oxygen reduction electrocatalyst of cobalt monatomic isolated platinum nanoparticles and preparation method of oxygen reduction electrocatalyst
CN115318322A
Preparation method and application of ZIF-67-ZIF-8 cobalt-based catalyst with core-shell structure
CN116586093A
Atomically dispersed metal catalysts and applications thereof
US20210316289A1